1976
DOI: 10.3109/00498257609151634
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol Metabolism in the Rat: Relationship to Covalent Binding and Hepatic Damage

Abstract: 1. The degree of liver damage observed 48 h after administration of 14C ring-labelled paracetamol (3-23 mmol/kg) to rats was proportional to the amount of a highly reactive metabolite retained in the liver, bound covalently to hepatocellular proteins. 2. With increasing doses of paracetamol, urinary excretion of the glucuronide and sulphate conjugates reached a plateau, whereas the output of cysteine and mercapturic acid conjugates increased markedly. 3. The degree of covalent binding at 48 h was proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Acetaminophen and 7-hydroxycoumarin have been reported to be metabolized primarily through glucuronidation and sulfation in the rat (Davis et al, 1976;Wang et al, 2005). UGT activity was determined in RLM (4 mg/ml), using acetaminophen (2 M) or 7-hydroxycoumarin (50 M) as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Acetaminophen and 7-hydroxycoumarin have been reported to be metabolized primarily through glucuronidation and sulfation in the rat (Davis et al, 1976;Wang et al, 2005). UGT activity was determined in RLM (4 mg/ml), using acetaminophen (2 M) or 7-hydroxycoumarin (50 M) as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…The same trend may also be seen by comparing our data with that of Jollow et al (7) who used male Sprague-Dawley rats. Again Davis et al (8) have shown that male Wistar rats produce more Female (19) Male (19) Female" Male ( mercapturic acid than do females of that species. In their study they found that males developed grade 2 hepatic necrosis following a dose of 10 mmole/kg (Table XIV).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant metabolic difference was the trend to decreased PM and increased 3SMeP and 3SMePG. Wistar rats were included in this study since other authors (8,19) have referred to their handling of paracetamol and thus they provide interesting controls for Sprague-Dawley rats. Furthermore they are required as controls in studies of the metabolism of paracetanol in Gunn rats (26) which are a mutant strain of Wistars.…”
Section: Female Wistar Ratsmentioning
confidence: 99%
See 2 more Smart Citations